2022
DOI: 10.1093/nar/gkac359
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-specific insertions in T-box riboswitches modulate antibiotic binding and action

Abstract: T-box riboswitches (T-boxes) are essential RNA regulatory elements with a remarkable structural diversity, especially among bacterial pathogens. In staphylococci, all glyS T-boxes synchronize glycine supply during synthesis of nascent polypeptides and cell wall formation and are characterized by a conserved and unique insertion in their antiterminator/terminator domain, termed stem Sa. Interestingly, in Staphylococcus aureus the stem Sa can accommodate binding of specific antibiotics, which in turn induce robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In this work, we identified transit structure and determined the distinct folding patterns of the SAM-VI riboswitch in the absence and presence of the ligand, which facilities to reveal the structural basis for “switching” in signal transmission and regulatory mechanism of riboswitches, which has remained a mystery since their discovery for more than twenty years ago. In addition, the distinct switching pattern of riboSAM during synthesis can provide a structural basis for antibacterial drug design targeting this riboswitch 60 , 61 . With the capability of introducing various modifications and obtaining nascent transcripts of desired lengths, our strategy can flexibly cooperate with detection methods to study RNAs when appropriate modifications are incorporated, such as isotopes and spin labels for NMR and EPR, 2’-hydroxyl acylation for SHAPE.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we identified transit structure and determined the distinct folding patterns of the SAM-VI riboswitch in the absence and presence of the ligand, which facilities to reveal the structural basis for “switching” in signal transmission and regulatory mechanism of riboswitches, which has remained a mystery since their discovery for more than twenty years ago. In addition, the distinct switching pattern of riboSAM during synthesis can provide a structural basis for antibacterial drug design targeting this riboswitch 60 , 61 . With the capability of introducing various modifications and obtaining nascent transcripts of desired lengths, our strategy can flexibly cooperate with detection methods to study RNAs when appropriate modifications are incorporated, such as isotopes and spin labels for NMR and EPR, 2’-hydroxyl acylation for SHAPE.…”
Section: Discussionmentioning
confidence: 99%
“…A probing analysis showed that tigecycline induced protection on multiple previously known and new sites, a discovery that explains why the mutant of G. kaustophilus glyQ T-box appended with stem Sa increased in vivo the transcription readthrough in the presence of tigecycline. In conclusion, Staphylococcal -specific stem Sa can serve as a potential lineage-specific drug target since it facilitates the binding and function of protein synthesis inhibitors [ 30 ]. These recent observations, taken together, strongly suggest that targeting T-box riboswitches can be both species-specific and effective, thus, providing a proof-of-concept for the development of new inhibitors that interfere with specific RNA structural features.…”
Section: T-box Riboswitchesmentioning
confidence: 99%
“…For instance, some riboswitches that are widely distributed among different bacterial species (i.e., TPP, FMN riboswitches) could be used as broad-spectrum antibacterial targets, while others that are found specifically in individual genus or species could constitute selective drugs (e.g., targeting preQ-1 or purine-riboswitches) [ 26 ]. Recently, it was reported that T-boxes in Staphylococcus aureus contain species-specific structural features that play a central role in riboswitch structural conformation and function, allowing the adaptation to specific metabolic environments, making them promising, lineage-specific drug targets [ 27 , 28 , 29 , 30 ]. Furthermore, some riboswitches regulate the expression of several genes that are fundamental for bacterial survival.…”
Section: Introductionmentioning
confidence: 99%